The Sustainability of Commercial Tour Operations in Protected Natural Areas: defining categories of environmental supply - McNicol, Barbara (Anais Brasileiros de Estudos Turísticos, 2016)
There is a need in federally protected areas, such as national parks, to investigate the connection between management actions and responsible and sustainable tourism. Environmental supply, as a subset of ecosystem services, is a recent concept that seeks to contribute positively to park management actions about commercial visitor activities and environmental conservation in protected national areas. This can be accomplished by linking commercial visitor demand with understanding of tour operator’s views about environmental supply. This study targets commercial tour operator’s categorization of environmental supply in the Canadian Rocky Mountain national parks of Banff and Jasper. As a concept, environmental supply includes natural features, physical attributes, management initiatives and/or governance policies that influence environmental conservation. Environmental supply, therefore, will include the ecosystems and services of the park destination, visitor education and interpretive programs, zoning and access, environmental impact assessment (EIA) procedures, policies and guidelines, and any other characteristics and initiatives that impact the conservation and/or preservation of nature at a visitor-centered site. How commercial tour operators respond to and manage these for environmental protection in a conservation environment will determine tourism sustainability at the destination. This research presents the results of interviews and a pilot survey that provided information to create initial categories of quality success of environmental supply as defined by commercial tour operators in Banff and Jasper National Parks in the Rocky Mountains of Canada. The goal of this research is to provide a methodology to monitor changes over time by using categories of this research to define quality success indicators of environmental supply that are also parameters of sustainability in high use national parks.